2021
DOI: 10.1523/jneurosci.3067-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relations between Cortical Network Oscillations and Breathing Frequency during REM Sleep

Abstract: Nasal breathing generates a rhythmic signal which entrains cortical network oscillations in widespread brain regions on a cycle-to-cycle time scale. It is unknown, however, how respiration and neuronal network activity interact on a larger time scale: are breathing frequency and typical neuronal oscillation patterns correlated? Is there any directionality or temporal relationship? To address these questions, we recorded field potentials from the posterior parietal cortex of mice together with respiration durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 105 publications
3
30
1
Order By: Relevance
“…Instead, a recent study has demonstrated that the direction of causality is from theta to respiration and not the reverse. This study also found evidence for a peripheral reafference signal in gamma oscillations, however, [36]. This peripheral reafference as well as studies showing that oral respiration can play a role [34] must be reconciled in this emerging field.…”
Section: Introductionsupporting
confidence: 59%
“…Instead, a recent study has demonstrated that the direction of causality is from theta to respiration and not the reverse. This study also found evidence for a peripheral reafference signal in gamma oscillations, however, [36]. This peripheral reafference as well as studies showing that oral respiration can play a role [34] must be reconciled in this emerging field.…”
Section: Introductionsupporting
confidence: 59%
“…The temporal relationships between brain activity and the physiological signal are frequency dependent. For example, in mice, theta oscillations precede and are Granger-causal for the variation of respiration rate, whereas it is the opposite for the gamma oscillations (84). Our results support that at frequencies <0.5 Hz, the information mainly flows from brain to heart rate, outweighing the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
“…These relationships between respiration and cognitive processes suggest a specific role for respiration as a timing signal for brain activity 69 . For instance, it has been shown that the respiratory rate shapes olfactory memory 70,71 , emotions 72 , and reaction time 73 , and coordinates the coupling of brain oscillations during sleep [74][75][76] as well as during wakefulness [77][78][79][80][81][82] . These results indicate that cardiorespiratory activity contribute to the shaping of attention and perception, and relative changes in respiration and heart rates are part of ongoing bidirectional brain-heart interplay processes 83 , similar to emotions or stress 84,85 .…”
Section: Monitoring Of Visceral Activitymentioning
confidence: 99%